2013
DOI: 10.1017/jns.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Score and prostate cancer risk in a Swedish population-based case–control study

Abstract: Several individual components of the Mediterranean diet have been shown to offer protection against prostate cancer. The present study is the first to investigate the association between adherence to the Mediterranean diet and the relative risk of prostate cancer. We also explored the usefulness of the Mediterranean Diet Score (MDS) in a non-Mediterranean population. FFQ data were obtained from 1482 incident prostate cancer patients and 1108 population-based controls in the Cancer of the Prostate in Sweden (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
1
25
1
2
Order By: Relevance
“…Two recent studies assessed the relationship between this dietary pattern and prostate cancer incidence specifically, and neither found any significant association (7,8). Although Möller et al considered several versions of the Mediterranean diet score they found little support for any association between the Mediterranean diet and prostate cancer (8). The Mediterranean dietary pattern identified in our Swedish population was not extensively Mediterranean, and it is therefore possible that potential protective levels of intake were not reached.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Two recent studies assessed the relationship between this dietary pattern and prostate cancer incidence specifically, and neither found any significant association (7,8). Although Möller et al considered several versions of the Mediterranean diet score they found little support for any association between the Mediterranean diet and prostate cancer (8). The Mediterranean dietary pattern identified in our Swedish population was not extensively Mediterranean, and it is therefore possible that potential protective levels of intake were not reached.…”
Section: Discussionmentioning
confidence: 59%
“…The traditional Mediterranean diet has, because of its content of foods and nutrients with proposed protective effects, been suggested to decrease the risk of prostate cancer (50,51). Two recent studies assessed the relationship between this dietary pattern and prostate cancer incidence specifically, and neither found any significant association (7,8). Although Möller et al considered several versions of the Mediterranean diet score they found little support for any association between the Mediterranean diet and prostate cancer (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that of the negative studies three were undertaken in nonMediterranean populations; USA, Sweden and Holland (11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Dans aucune de ces trois études, Nord-Européenne, cas-témoins [27], et Nord-Américaines, prospectives [28,29] utilisant le M-MDS et/ou l'a-MDS, il n'existe d'association entre l'adhésion à l'alimentation méditerranéenne ainsi évaluée et le risque de cancer de la prostate. Dans une étude a posteriori sur une cohorte Australienne, aucune association n'a pu être mise en évidence entre un profil alimentaire et le cancer de la prostate [30]. On manque d'études étudiant la relation cancer de la prostate et alimentation méditerranéenne dans un pays méditerranéen.…”
Section: Cancer De La Prostateunclassified